Measuring and evaluating colorimetric properties of samples from loess-paleosol sequences - Laag, Christian; Lagroix, France; Kreutzer, Sebastian; Chapkanski, Stoil; Zeeden, Christian; Guyodo, Yohan (MethodsX, 2023)
Colorimetric measurements are valuable in studying paleoenvironmental changes in sediment archives such as loess-paleosol sequences. These measurements allow for the identification of climate-sensitive minerals such as hematite, goethite, and secondary carbonates, as well as the observation of stratigraphic changes influenced by paleoclimate variations. Herein, a detailed workflow protocol emphasizing mineral abundance extraction by determining true band amplitudes is presented. Moreover, we present a protocol for colorimetric measurements that eliminates container bias, allowing the analysis and re-analysis of stored sediment quickly and inexpensively. Finally, we introduce a new R-package ('LESLIE') for graphical data display and enhancement. The protocol and its validation are demonstrated on the Suhia Kladenetz loess-paleosol sequence of northern Bulgaria.•A detailed workflow protocol eliminating container bias in colorimetric measurements and extracting mineral abundances is presented.•The protocol is independently validated with aid of Attenuated Total Reflectance Fourier Transform mid-infrared (ATR-FTIR) spectroscopic experiments.•Stratigraphic color enhancement using the R-package 'LESLIE' is facilitated by a user-friendly R-shiny application.
Gesehen am 04.06.2024